2016
DOI: 10.1007/s11095-016-2088-9
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Polymersomes as Nanocarriers for Doxorubicin Hydrochloride: Enhanced Cytotoxicity in MCF-7/ADR Cells and Prolonged Blood Circulation

Abstract: The entrapment of DOX in biodegradable polymersomes could enhance cytotoxicity in MCF-7/ADR cells and improve its in vivo pharmacokinetic profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…The simultaneous encapsulation of 5-FU, Dox and LV eliminates their solution incompatibilities and allows their simultaneous administration with enhanced therapeutic effect. The encapsulation efficiency of all the compounds was greater than 70 % (Table 1) and in agreement with similar studies reported in the literature [41,42].…”
Section: Characterisation and Evaluation Of Polymersomessupporting
confidence: 91%
“…The simultaneous encapsulation of 5-FU, Dox and LV eliminates their solution incompatibilities and allows their simultaneous administration with enhanced therapeutic effect. The encapsulation efficiency of all the compounds was greater than 70 % (Table 1) and in agreement with similar studies reported in the literature [41,42].…”
Section: Characterisation and Evaluation Of Polymersomessupporting
confidence: 91%
“…The pharmacokinetic study in male SD rats showed that entrapment of DOX in polymersomes resulted in the prolongation of drug t 1/2 by 4.54-fold, and the increase in AUC by 5.97-fold compared with free drug. These pharmacokinetic changes significantly enhanced cytotoxicity and reduced resistance of MCF-7/ADR cells to DOX 14. An improved pharmacokinetic profile of DOX and its cytotoxicity were also reported when loaded in chitosan-g-TPGS (CT).…”
Section: Resultsmentioning
confidence: 91%
“…The anthracycline antibiotics doxorubicin (DOX) and daunorubicin (DNR) are broadly used for the treatment of a variety of cancers. They exert their action on cancer cells by intercalation into DNA base pairs resulting in blockage of DNA and RNA synthesis and DNA scission, which suppresses the replication of DNA and induces cell apoptosis 14. The pharmacokinetic study in male SD rats showed that entrapment of DOX in polymersomes resulted in the prolongation of drug t 1/2 by 4.54-fold, and the increase in AUC by 5.97-fold compared with free drug.…”
Section: Resultsmentioning
confidence: 99%
“…Later on, Chao, et al. successfully generated doxurubicin (DOX)‐loaded polymersomes in nanoscale (60 nm in diameter) by using methoxy poly(ethylene glycol)‐b‐poly(epsilon‐caprolactone) (mPEG‐b‐PCL) . The use of film hydration method for polymersome formation was still very popular, which was being scrutinized in recent reports .…”
Section: Common Methods For Preperation Of Polymeric Hollow Capsulesmentioning
confidence: 99%